The Use of Design Thinking in IT Project Management - Chomiak-Orsa, Iwona; Łuczak, Kamila (Wykorzystanie Design Thinking w zarządzaniu projektami informatycznymi, 2022)
Faced with many challenges related to product competitiveness, companies are constantly looking for new ways to solve problems and provide innovative solutions. Problems in IT projects, which are characterised by a higher degree of complexity, may be particularly difficult to solve. The Design Thinking (DT) concept can be a response to the challenges of an organization. The aim of the article is to discuss the application of the Design Thinking method in IT project management. The article examines content related to the creative approach of DT, the basics of project management and the application of Design Thinking in two IT organizations – Apple and IBM. Research methods such as literature analysis and case study will be used. Based on the conducted research, it can be concluded that the use of the Design Thinking concept in IT project management can generate many benefits for companies.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 2 (64), s. 10-18
Keywords: design thinking; IT project management; Apple; IBM; zarządzanie projektami informatycznymi